2021
DOI: 10.1002/hep4.1831
|View full text |Cite
|
Sign up to set email alerts
|

Community Socioeconomic Deprivation Predicts Nonalcoholic Steatohepatitis

Abstract: In order to determine the relationship between socioeconomic deprivation and nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH), we retrospectively reviewed the electronic medical records of 1,430 patients in a large tertiary health care network in New York. These patients underwent liver biopsy over a 10-year period and were included in our study if they had evidence of NAFLD/NASH on liver biopsy. Zip codes were used to obtain data necessary to derive the social deprivation index (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Growing evidence suggests that socio-economic status is inversely related to the prevalence of NAFLD [ 62 65 ], and that lower incomes and education levels are associated with worse liver outcomes [ 66 ]. Social status has a significant influence in predicting NAFLD, and during routine clinical practice, those who belong to lower social classes should be accurately screened for a possible higher risk [ 66 ]. The social class effect on health and disease has been observed to possibly start from early adolescence and diminish with increasing age [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that socio-economic status is inversely related to the prevalence of NAFLD [ 62 65 ], and that lower incomes and education levels are associated with worse liver outcomes [ 66 ]. Social status has a significant influence in predicting NAFLD, and during routine clinical practice, those who belong to lower social classes should be accurately screened for a possible higher risk [ 66 ]. The social class effect on health and disease has been observed to possibly start from early adolescence and diminish with increasing age [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging data suggest that neighbourhood-level SDOH may affect both the development and progression of SLD. 6,7 Chen et al 8 have expanded on this work by examining the association between two well established neighbourhood-level SDOH ('disadvantage' and 'affluence') and clinical outcomes among patients with metabolic dysfunction-associated SLD (MASLD) seen at a single centre in Michigan. Increased neighbourhood disadvantage was associated with higher mortality and incident cardiovascular disease (CVD); higher neighbourhood affluence was associated with lower mortality, CVD and liver-related events (LRE).…”
Section: Editorial: Social Determinants Of Health In Steatotic Liver ...mentioning
confidence: 99%
“…Additionally, it was interesting to find that NAFLD individuals were less likely to be smokers. However, the negative association between NAFLD and smoking should be interpreted with caution as previous studies have reported contrasting associations between smoking and NAFLD [40][41][42] , and the effect of smoking may be too premature to manifest in young adults. Interestingly, lower income levels are also significantly associated with NAFLD diagnosis.…”
Section: Discussionmentioning
confidence: 90%